2013
DOI: 10.7863/jum.2013.32.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Increased Enthesopathy in Patients With Familial Mediterranean Fever

Abstract: This study showed significant enthesopathy in patients with familial Mediterranean fever. The findings support the hypothesis that familial Mediterranean fever and spondyloarthropathy may have common inflammatory mechanisms and suggest that the MASEI scoring system can be incorporated into clinical protocols for studying patients with familial Mediterranean fever in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
1
5
1
2
Order By: Relevance
“…The link between tendinopathy and FMF has been a debate. Some studies concluded that there is a link between enthesopathy and FMF [2,3,5]. The most striking finding of our study was no statistically significant difference was reached in terms of tendon thickness or SE grading of Achilles tendon enthesopathy.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The link between tendinopathy and FMF has been a debate. Some studies concluded that there is a link between enthesopathy and FMF [2,3,5]. The most striking finding of our study was no statistically significant difference was reached in terms of tendon thickness or SE grading of Achilles tendon enthesopathy.…”
Section: Discussioncontrasting
confidence: 61%
“…On the other hand, no difference was observed between patients' and controls' MASEI scores and disease duration or colchicine treatment duration. Additionally, no difference was observed between the MASEI score and the presence or absence of arthritic involvement among the patients [5].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In literature, in addition to SpA, enthesitis was investigated only in few diseases including Behçet's disease [24,25], familial Mediterranean fever [26,27], Sjögren syndrome [28], dialysis patients [29], fibromyalgia [30,31], psoriasis [9,32], inflammatory bowel disease without spondyloarthritis symptoms [33] by using US. Although musculoskeletal involvement in SSc was investigated in a few studies by using US [34][35][36] with SSc by using MRI [7].…”
Section: Discussionmentioning
confidence: 99%
“…This association is reinforced by the particular frequency of enthesopathies in subjects with FMF [ 12 ] suggesting that the mutant MEFV gene could partially promote such an association [ 11 , 13 ].…”
Section: Familial Mediterranean Fever and Its Most Frequent Associatimentioning
confidence: 99%